2018
DOI: 10.1111/efp.12444
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of vegetative compatibility and mating types of Cryphonectria parasitica in İzmir, Manisa and Denizli provinces in western Turkey

Abstract: To extend our knowledge of population structure of Cryphonectria parasitica in the Aegean region, 264 isolates obtained from eight subpopulations in Izmir, Manisa and Denizli provinces were studied. Only three vegetative compatibility (vc) types, EU‐1, EU‐12 and EU‐2, were identified. EU‐1 (59%) was dominant and was found in all eight subpopulations. EU‐12 (32%) was detected in six subpopulations and was highly dominant (71%) in the Ödemiş subpopulation (İzmir province). EU‐2 was restricted to only one subpopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Lack of perithecia on the bark samples supports the hypothesis that C. parasitica population is clonal in western Turkey. In the past, low vc type diversity in the C. parasitica population in western Turkey was mostly associated with the lack of sexual reproduction (Daldal et al., 2018; Erincik et al., 2008, 2011). In our study, even though both MAT‐1 and MAT‐2 were found in all the five sampled sites, chi‐square values in four sites indicated that the mating‐type ratio significantly deviated from 1:1.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lack of perithecia on the bark samples supports the hypothesis that C. parasitica population is clonal in western Turkey. In the past, low vc type diversity in the C. parasitica population in western Turkey was mostly associated with the lack of sexual reproduction (Daldal et al., 2018; Erincik et al., 2008, 2011). In our study, even though both MAT‐1 and MAT‐2 were found in all the five sampled sites, chi‐square values in four sites indicated that the mating‐type ratio significantly deviated from 1:1.…”
Section: Discussionmentioning
confidence: 99%
“…EU1/MAT1 and EU12/MAT2 were not used since EU12/MAT2 was a rare genotype in western Turkey. Crosses were conducted on autoclaved pieces of chestnut wood embedded in potato dextrose agar (Figure 1) (Cortesi & Milgroom, 1998; Daldal et al., 2018). To prepare media, chestnut wood pieces, about 2–3 cm in diameter and 5 cm in length, were split equally longitudinally and the bark side of each piece was scraped lengthwise with a razor blade to create 5–6 parallel scrapes before autoclaving.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations